The Ultrasonic P-Wave Velocity-Stress Relationship and Energy Evolution of Sandstone under Uniaxial Loading-Unloading Conditions - Long Zhang; Zetian Zhang; Ru Zhang; Mingzhong Gao; Jing Xie (Advances in Materials Science and Engineering)
As shallow resources are exhausted, deep resources are gradually being exploited; consequently, mining disasters and accidents have increased significantly over time. During mining, a deep rock mass experiences complex mining-induced stress evolution, damage accumulation, and deformation failure processes, and the mechanical and acoustic properties of the rock constantly change. To better understand the variation in the mechanical and acoustic properties of rock under loading and unloading conditions, uniaxial loading-unloading experiments with real-time ultrasonic P-wave velocity monitoring were conducted on sandstone specimens drilled from a coal seam roof. The test results show that the axial stress level is directly related to the P-wave velocity. A logarithmic relationship exists between the ultrasonic P-wave velocity and stress in the tested sandstones. The wave velocity increase caused by the unit axial pressure increase is significantly lower than that at the initial loading stage after entering the higher stress level. The energy evolution of sandstone during loading and unloading is closely related to the stress loading history and reflects the damage accumulation in the rock. Under elastic loading, the energy accumulation is mainly reflected by an increase in elastic energy, and less energy is dissipated during the elastic loading period. Stress unloading causes high energy dissipation, resulting in irreversible strain and damage accumulation, which provides a good basis for using ultrasonic testing to preliminarily judge the failure of a specific rock and formulate corresponding engineering measures.